Reservoir frogs: seasonality of Batrachochytrium dendrobatidis infection in robber frogs in Dominica and Montserrat - Hudson, Michael A. (PeerJ, 2019)
Emerging infectious diseases are an increasingly important threat to wildlife conservation, with amphibian chytridiomycosis, caused by Batrachochytrium dendrobatidis, the disease most commonly associated with species declines and extinctions. However, some amphibians can be infected with B. dendrobatidis in the absence of disease and can act as reservoirs of the pathogen. We surveyed robber frogs (Eleutherodactylus spp.), potential B. dendrobatidis reservoir species, at three sites on Montserrat, 2011–2013, and on Dominica in 2014, to identify seasonal patterns in B. dendrobatidis infection prevalence and load (B. dendrobatidis genomic equivalents). On Montserrat there was significant seasonality in B. dendrobatidis prevalence and B. dendrobatidis load, both of which were correlated with temperature but not rainfall. B. dendrobatidis prevalence reached 35% in the cooler, drier months but was repeatedly undetectable during the warmer, wetter months. Also, B. dendrobatidis prevalence significantly decreased from 53.2% when the pathogen emerged on Montserrat in 2009 to a maximum 34.8% by 2011, after which it remained stable. On Dominica, where B. dendrobatidis emerged seven years prior to Montserrat, the same seasonal pattern was recorded but at lower prevalence, possibly indicating long-term decline. Understanding the dynamics of disease threats such as chytridiomycosis is key to planning conservation measures. For example, reintroductions of chytridiomycosis-threatened species could be timed to coincide with periods of low B. dendrobatidis infection risk, increasing potential for reintroduction success.